Pengaruh metode latihan multiball terhadap ketepatan pukulan backhand drive tenis meja - shinta putria rehendra; Yogi Andria; Donal Syafrianto; sonya nelson (Jurnal IKEOR, 2024)
The problem in this study was the poor backhand accuracy of PTM table tennis player Sawah Liat Nanggalo. The aim of this study was to determine the effect of multi-ball training on the backhand accuracy of table tennis players at PTM Sawah Liat Nanggalo. This type of study is an approximate test. This study was carried out at PTM Sawah Liat Nanggalo, while this study was conducted in July-August 2023. The sample for this study were table tennis players at PTM Sawah Liat Nanggalo, total of 8 people. Technical data collection with ping pong backhand accuracy test. Data were analyzed by different statistical tests (t test) with significance level α = 0.05. The research results obtained are as follows: The standard value for the pre-test is 0.2726 < 0 >1.89 ttable. (Meaningful).